Upskilling Higher Education Students for Digital Competency Using Project Based Learning - Nurkholida, Erna; Sahari, Annisa Aulia; Ulfah, Ulin Ni'mah Rodliya (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
Students in the 21st century are emphasized to master digital skills to support their education. Students majoring in English education besides mastering English, they must also be able to teach on a digital platform The problem of this research is how to strengthen digital competence in IAIN Kediri students through Project Based Learning. This research aims to improve the digital competence skills of English study program students through the Project Based Learning method. Strengthening was carried out in the Teaching English for Young Learners class using Classroom Action Research in 6 meetings. With the strengthening of the class, focused on digital competence namely Google Site, Canva Poster, Quizzis and White Board Animation. The projects are designing Learning Englsih Website for Elementary Students using Google Site and Canva Poster, Developing Listening material and exercises using Quizziz and Canva, constructing speaking material using White board Animation, speaking exercises using Quizziz and Canva, Designing writing material using Quizziz and Canva speaking exercises using Quizzis and Canva, Designing writing material using Quizzis, White Board Animation and Canva Poster. All project results from strengthening digital competencies based on project-based learning are published in the following link: https://sites.google.com/view/teylclass/, after being checked by the instructor with satisfactory and good results.